An e-Recruitment System Exploiting Candidates’ Social Presence - Faliagka, Evanthia; Rigou, Maria; Sirmakessis, Spiros (Current Trends in Web Engineering, 2015)
Applicant personality is a crucial criterion in many job positions. Choosing applicants whose personality traits are compatible with job positions has been shown to increase their satisfaction levels, as well as the rate of employee retention. However, the task of assessing candidates’ personality is not addressed in today’s online recruitment systems, but is typically handled during the interview process. The rapid deployment of social web services has made candidates’ social activity much more transparent, giving us the opportunity to infer features of candidate personality with web mining techniques. In this work, a novel approach is proposed and evaluated for automatically extracting candidates’ personality traits based on their social media use.